MECHANISM OF THE FORMATION OF OIL AND GAS POOLS - Barenbaum A.A. (My University, 2004)
The proposed mechanism of oil-gas pool formation is based on three processes: (1) the essential role of the climatic water cycle in carbon transfer to subsurface reservoirs; (2) the reduction of oxidized carbon forms in the Earth's crust to hydrocarbons as a free phase; (3) the physicochemical transformation of hydrocarbons and their accumulation as oil and gas in traps.